Reducing the addictiveness of cigarettes: This report was presented by the American Medical Association (AMA) Council on Scientific Affairs to the AMA House of Delegates at its 147th annual meeting in June 1998. The recommendations at the end of the report were adopted by the House as AMA policy. Issue 3 (1st September 1998) - Henningfield, Jack E; Benowitz, Neal L; Slade, John; Houston, Thomas P; Davis, Ronald M; Deitchman, Scott D
Abstract : OBJECTIVE: To assess the feasibility of reducing tobacco-caused disease by gradually removing nicotine from cigarettes until they would not be effective causes of nicotine addiction. DATA SOURCES: Issues posed by such an approach, and potential solutions, were identified from analysis of literature published by the US Food and Drug Administration (FDA) in its 1996 Tobacco Rule, comments of the tobacco industry and other institutions and individuals on the rule, review of the reference lists of relevant journal articles, other government publications, and presentations made at scientific conferences. DATA SYNTHESIS: The role of nicotine in causing and sustaining tobacco use was evaluated to project the impact of a nicotine reduction strategy on initiation and maintenance of, and relapse to, tobacco use. A range of potential concerns and barriers was addressed, including the technical feasibility of reducing cigarette nicotine content to non-addictive levels, the possibility that compensatory smoking would reduce potential health benefits, and whether such an approach would foster illicit ("black market") tobacco sales. Education, treatment, and research needs to enable a nicotine reduction strategy were also addressed. The Council on Scientific Affairs came to the following conclusions: (a) gradually eliminating nicotine from cigarettes is technically feasible; (b) a nicotine reduction strategy holds great promise in preventing adolescent tobacco addiction and assisting the millions of current cigarette smokers in their efforts to quit using tobacco products; (c) potential problems such as compensatory over-smoking of denicotinised cigarettes and black market sales could be minimised by providing alternate forms of nicotine delivery with less or little risk to health, as part of expanded access to treatment; and (d) such a strategy would need to be accompanied by relevant research and increased efforts to educate consumers and health professionals about tobacco and health. CONCLUSIONS: The council recommends the following: (a) that cessation of tobacco use should be the goal for all tobacco users; (b) that the American Medical Association continue to support FDA authority over tobacco products, and FDA classification of nicotine as a drug and tobacco products as drug-delivery devices; (c) that research be encouraged on cigarette modifications that may result in less addicting cigarettes; (d) that the FDA require that the addictiveness of cigarettes be reduced within 5–10 years; (e) expanded surveillance to monitor trends in the use of tobacco products and other nicotine-containing products; (f) expanded access to smoking cessation treatment, and strengthening of the treatment infrastructure; and (g) more accurate labelling of tobacco products, including a more meaningful and understandable indication of nicotine content.